Effect of temperature on growth of the pathogenic oomycete pythium insidiosum - Theerapong Krajaejun (2018)
Pythium insidiosum causes a potentially life-threatening infectious disease called pythiosis. An early, accurate diagnosis is important, since prompt treatment leads to a better prognosis. Unsuccessful attempts to isolate the organism have been associated with specimens subjected to lower temperatures. We analyzed growth of P. insidiosum at various temperatures. Culture at low (8°C) and high (42°C) temperatures resulted in death or inhibited growth of the organism. Culture under optimal temperatures (28 and 32°C) was important for successful isolation of P. insidiosum.